2013
DOI: 10.1038/jid.2013.170
|View full text |Cite
|
Sign up to set email alerts
|

The IL23R A/Gln381 Allele Promotes IL-23 Unresponsiveness in Human Memory T-Helper 17 Cells and Impairs Th17 Responses in Psoriasis Patients

Abstract: We and others have shown that the minor, nonconserved allele Gln381 of the Arg381Gln single-nucleotide polymorphism (rs11209026G>A) of the IL-23 receptor gene (IL23R) protects against psoriasis. Moreover, we have recently shown impaired IL-23-induced IL-17A production and STAT-3 phosphorylation in Th17 cells generated in vitro from healthy individuals heterozygous for the protective A allele (GA). However, the biological effect of this variant has not been determined in homozygous carriers of the protective A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 40 publications
(58 reference statements)
1
37
1
Order By: Relevance
“…The protective variant rs11209026 results in a R381Q substitution and functional studies in healthy individuals showed the variant to be a loss of function leading to impaired Th17 effector responses (Di Meglio et al, 2011;Pidasheva et al, 2011;Sarin et al, 2011). In concordance with these data, recent studies showed that genetic variations in genes involved in the IL-23 signalling pathway influence the effector function of Th17 and Th1 cells in patients with AS and in patients with the related skin disease psoriasis (Coffre et al, 2013;Di Meglio et al, 2013). Interestingly, SNPs in IL-23R as well as in IL-23 are also associated with PsA, a distinct phenotypic subset of SpA (Bowes et al, 2011;Filer et al, 2008).…”
Section: Geneticsmentioning
confidence: 76%
“…The protective variant rs11209026 results in a R381Q substitution and functional studies in healthy individuals showed the variant to be a loss of function leading to impaired Th17 effector responses (Di Meglio et al, 2011;Pidasheva et al, 2011;Sarin et al, 2011). In concordance with these data, recent studies showed that genetic variations in genes involved in the IL-23 signalling pathway influence the effector function of Th17 and Th1 cells in patients with AS and in patients with the related skin disease psoriasis (Coffre et al, 2013;Di Meglio et al, 2013). Interestingly, SNPs in IL-23R as well as in IL-23 are also associated with PsA, a distinct phenotypic subset of SpA (Bowes et al, 2011;Filer et al, 2008).…”
Section: Geneticsmentioning
confidence: 76%
“…Several studies have previously highlighted the importance of genes and haplotypes in both the IL-23 as well as the NF-B pathways in psoriasis (Nair et al, 2009;Safrany et al, 2011;Safrany et al, 2013) as well as in many other immune-mediated diseases; PsA (Di Meglio et al, 2013;Eiris et al, 2014;Nair et al, 2010;Cargill et al, 2007;Franke et al, 2010;Strange et al, 2010;Bowes et al, 2011;Liu et al, 2008;Popa et al, 2013;Wang et al, 2012;Capon et al, 2007), Crohn's disease (Chua et al, 2012;Dinu et al, 2012;Jung et al, 2012), inflammatory bowel disease (Duerr et al, 2006;Safrany et al, 2013), ankylosing spondylitis (Safrany et al, 2009), celiac disease and multiple sclerosis (Nunez et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…However, IFN-γ secretion by R381Q IL23R memory T cells was not affected. Additionally, the presence of R381Q IL23R gene polymorphism has been associated with unresponsiveness to IL-23 by human memory Th17 cells, impairing the Th17 response in psoriasis patients [46]. …”
Section: Il-23 Clinical Applicationsmentioning
confidence: 99%